IMPLEMENTASI KEBIJAKAN PENDIDIKAN LINGKUNGAN HIDUP SD NEGERI 3 PEKANBARU MENUJU SEKOLAH ADIWIYATA - MASLIAH NOVITA; SUMARNO SUMARNO; DAVIQ CHAIRILSYAH (Universitas Riau, 2017)
The purpose of this research to preserve the environment draught sustainablesaw now there have been and are morefrequent applied disekolah. Pendidikan environment(plh) is expected to be one of alternative solutions that is effective in efforts to improve theknowledge and understanding for preserving the the environmental functions .Education is oneform of a human culture a dynamic and laden development .Therefore , change or developmentof education is the that is supposed to happen in line with the changes culture life .Functioneducation as a developer and common the ability , personality , character , and civilizationnation a dignified in order mencerdaskan life the play an important role in infuse values educationenvironment to generation .Learning education environment that has now and are more frequentapplied in schools. Focus on research is the implementation of education policy environmentpublic primary schools 3 pekanbaru to school adiwiyata. By one that witnesses subfokus is a )implementation so that a policy can reach in accordance with its objectives, b ) the implementationof education life that is the decision-making process related to on the implementationof education policy environment.The purpose who were just about to achieved through thisstudy is to find and analyze the implementation of educationpolicy environment of public school3 pekanbaru adiwiyata to school , methods used is to use the qualitative method because , theproblems it was not immediately clear , holistic , complex , dynamic and full of meaning makingit impossible data on social situations were captured by the method of quantitative researchwith an instrument like test , the questionnaire , guidelines wawancara.selain it , researchersmean to understand social situation in depth , discover patterns , hypothesis and teori.teoriObjectresearch it will be the implementation of education policy living environment consisting of thecommunication, resources, disposition, and bureaucratic structure .metode data collection isobservation, Interview, and documentation of .data conclusion. The research results show thatthe implementation of education policy environment in public primary schools 3 pekanbarubeen successful in the application and pelaksaannya, because of public school 3Do yaangsufficient , attitude executives and target policy that is students was also very support and theavailability of regulations have very support namaun there are obstacles in implement thispolicy , between some are still the absence of a laboratory for melangkapi activity that isrelated to the environment , the number of people of parents and a member of a committeewhich to gotong royong and other activities still not in quantity are numerous and , there aremany students who stay in gotong royong seara full of or to completion .